Absolute Mean Graceful Labeling in Various Graphs - V. J. Kaneria; H. P. Chudasama (International Journal of Mathematics And its Applications, 2017)
In the pesent study of paper, we defined absolute mean graceful labeling for various graphs. We proved all path graphs $P_{n}$, cycle $C_{n}$, complete bipartite graph $K_{m,n}$, grid graph $P_{m}× P_{n}$, step grid graph $St_{n}$ and double step grid graph $ DSt_{n}$ are absolute mean graceful graphs.